Meeting the challenges imposed by COVID-19: Guidance document by the ESTRO Radiation TherapisT Committee (RTTC) (2020)
COVID-19 – a novel coronavirus was firstly reported in December 2019. In response to threats imposed by COVID-19, the European society for radiotherapy and oncology Radiation TherapisT Committee (ESTRO RTTC) prepared this document in conjunction with an infographic with four main domains: patient care, RTT workflow, remote working and RT practice. In the context of the current COVID-19 pandemic, RTTs should be empowered with appropriate guidance and personal protection equipment in order to provide a safe radiotherapy service by limiting potential viral exposure to patients, healthcare workers and general public.